A Study to Assess Resilience and Empathy among the BSc Nursing Students - S. Anand; K. R. Anoopa; J. P Haripriya (Indian Journal of Psychiatric Nursing)
Introduction: Resilience is a crucial trait for nursing students as they navigate through the challenges and demands of their education and future profession. This cross-sectional study aimed to explore the levels of resilience and empathy among BSc nursing students. Methodology: The study was conducted under a quantitative approach and cross-sectional study design. BSc nursing students of Bishop Benziger College of Nursing, Kollam, were the sample. The purposive sampling technique is used for the selection of the sample. Standardized self-administered questioners were used to collect the data. Results: Analysis of socioeconomic variables reveals that majority of the samples were females (92.8%). Moreover, 79.9% belong to the Christian community. Most of the participants were aged 21 and above. The Percentage of the student in the first year is 27.3%, while the number who belongs to the 3rd year is 25.8% and equal number of students belongs to 4th year. Among 55% of participants were Hostlers and 69.6% had only one sibling. 37.6% of fathers and 23.2% of mothers have an education below 10th standard. Most of the participants (42.3%) reported a family income of below Rs. 10,000. More than 50% of the participants had average resilience and moderate empathy. The mean resilience score was 65.5 and the mean empathy score was 50.25. Positive strong correlations were found between the resilience and empathy of nursing college students. The study reveals a significant association between resilience and the year of studies, parent’s education, and family income of the participants at P < 0.05 level. In the same way, there was a significant association between empathy and the year of studies, parent’s education, and family income of the participants at P < 0.05 level. Conclusion: The study underscores the significance of resilience and empathy among BSc nursing students. It highlights the interconnectedness of these attributes and emphasizes the need for nursing education programs to focus on their cultivation. By developing resilience and empathy, nursing students can develop into competent and compassionate health-care professionals who can provide high-quality care to patients.